Pengaruh Fear of Missing Out (FoMO) dan Hedonic Shopping Motivation terhadap Impulsive Buying Produk Blind Box Pop Mart pada Generasi Z kota Bandung - Keisha Ath Thaariq; Nur Hayati (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2026)
The development of digital technology and social media has changed people's consumption behavior, especially Generation Z. One of the growing phenomena is the increasing popularity of blind box products among Generation Z in Indonesia. This study analyzes the influence of Fear of Missing Out (FoMO) and Hedonic Shopping Motivation on Impulsive Buying of Pop Mart blind box products among Generation Z in Bandung. This study applies a quantitative approach with a purposive sampling approach with 100 Generation Z respondents in Bandung aged 18-29 years. Data collection was carried out by distributing online surveys and data analysis was carried out with the help of SPSS software version 25 using multiple linear regression. The results of this study prove that Fear of Missing Out (FoMO) has a positive effect on Impulsive Buying. Hedonic Shopping Motivation also has a positive effect on Impulsive Buying. Simultaneously, it shows that Fear of Missing Out (FoMO) and Hedonic Shopping Motivation have a significant effect on Impulsive Buying (F count = 60.406, p <0.05) with an R2 value of 0.555. This indicates that the variables of Fear of Missing Out (FoMO) and Hedonic Shopping Motivation on Impulsive Buying are 55.5%, while the remaining 44.5% is influenced by other factors not included in this study.